INTERNAL IDENTITY ISSUES AFFECTING PAKISTAN'S FOREIGN POLICY. (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The article describes the influence of the internal problems of Pakistan's national identity on the state's foreign policy. Also, the importance of economic and terrorism-related problems in the country is revealed.